Thismia jianfenglingensis (Thismiaceae), a new species of fairy lantern from Hainan Island, China - Xu, Han; Yang, Haijun; Lin, Mingxian; Corrales, Adriana; Hogan, James Aaron; Li, Yide; Fang, Suqin (Phytotaxa, 2020)
A new species of Thismia (Thismiaceae), T. jianfenglingensis, is described and illustrated from Hainan Island, China. The new species is similar to T. hongkongensis, displaying a urecolate perianth tube, a loose dome with six perianth lobes, six stamens, and three stigmas. T. jianfenglingensis differs from T. hongkongensis in the color and morphology of perianth tube, the position of outer perianth lobes, the morphology and appendage of connective apex, the morphology of stigmas. The new species is only reported to occur on Hainan Island, China and it is proposed to be Vulnerable (VU) according to the IUCN criteria for the conservation status of plant species due to having a population with a very restricted area of occupancy or number of locations such that it is prone to become critically endangered or even extinct in a very short time period.